Pemaafan Bagi Anak Broken Home - Ain, Nurul; Mansyur, Ahmad Yasser; Lukman, Lukman (CV. Ulil Albab Corp, 2024)
This qualitative research using a case study approach model aims to find out about the conditions of broken homes experienced by children and to understand the form of forgiveness based on the perspective of children from broken homes. The research was conducted by interviewing 1 woman and 1 man as an early adult with a broken home family background. Determination of this subject was carried out using purposive sampling technique. Data collection in this research was by conducting semi-structured interviews conducted directly with sources based on interview guidelines that had been created and validated previously. The research results showed that the cause of broken homes in both subjects was divorce which occurred as a result of various factors ranging from quarrels to domestic violence. The separation of parents that occurs affects the relationship that exists between the subject and his parents and has its own impact on the subject. There are differences in the meaning of forgiveness between the two subjects which influence the application of forgiveness to the two subjects.